2015
DOI: 10.1007/s00262-015-1698-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel metronomic chemotherapy and cancer vaccine combinatorial strategy for hepatocellular carcinoma in a mouse model

Abstract: Hepatocellular carcinoma (HCC) is the most frequent primary liver cancer and represents the third and the fifth leading cause of cancer-related death worldwide in men and women, respectively. Hepatitis B virus (HBV) and hepatitis C virus (HCV) chronic infections account for pathogenesis of more than 80 % of primary HCC. HCC prognosis greatly varies according to stage at beginning of treatment, but the overall 5-year survival rate is approximately 5-6 %. Given the limited number of effective therapeutic strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 67 publications
1
23
0
Order By: Relevance
“…This was associated with the differentiation of naïve T-cells into central/effector memory cells (CM/ EM) and late differentiated poly-functional antigen-specific CD8 + T-cells in advanced ovarian cancer patients [76]. Similarly, metronomic administration of a high dose cocktail of chemotherapeutic agents (including cyclophosphamide, paclitaxel and docetaxel) during vaccination with a multi-peptide cocktail of peptides (comprising hepatitis C virus-derived antigens and tumor-associated antigens) resulted in an enhanced specific T-cell response and a reduced Treg frequency in hepatocellular carcinoma (HCC) patients [79]. Coadministration of gemcitabine with DC-based vaccines in a pancreatic carcinoma model showed a synergistic antitumor effect [116].…”
Section: Simultaneous Combination Of Chemotherapy With Vaccination Inmentioning
confidence: 99%
“…This was associated with the differentiation of naïve T-cells into central/effector memory cells (CM/ EM) and late differentiated poly-functional antigen-specific CD8 + T-cells in advanced ovarian cancer patients [76]. Similarly, metronomic administration of a high dose cocktail of chemotherapeutic agents (including cyclophosphamide, paclitaxel and docetaxel) during vaccination with a multi-peptide cocktail of peptides (comprising hepatitis C virus-derived antigens and tumor-associated antigens) resulted in an enhanced specific T-cell response and a reduced Treg frequency in hepatocellular carcinoma (HCC) patients [79]. Coadministration of gemcitabine with DC-based vaccines in a pancreatic carcinoma model showed a synergistic antitumor effect [116].…”
Section: Simultaneous Combination Of Chemotherapy With Vaccination Inmentioning
confidence: 99%
“…A large majority of these studies involve either short TAA-derived peptides that can directly bind to MHC Class I or II molecules expressed by antigen-presenting cells 176 (42 studies), or SLPs that are processed intracellularly and then loaded on MHC Class I or II molecules 172,177,178 (22 studies), most often in combination with immunological adjuvants 179-182 like montanide ISA-51 (water-in-oil emulsion) 181,183 Hiltonol® (poly- L -lysine in carboxymethylcellulose, a TLR3 ligand) 184 and GM-CSF. 183,185-187 In several instances, vaccination is further combined with standard treatment regimens including conventional chemotherapy, 117,188-191 radiation therapy, 52,192-195 and targeted anticancer agents, 196-199 or with various immunotherapeutic interventions. 200-205 The latter include (1) immune checkpoint blockers such as the anti-PD-1 mAbs pembrolizumab and nivolumab, 206-208 the anti-PD-L1 mAbs durvalumab and atezolizumab, 209-211 and the anti-CTLA4 mAb ipilimumab; 137,186,212-215 (2) immunostimulatory antibodies such as utomilumab, which stimulates TNF receptor superfamily member 9 (TNFRSF9; best known as 4-1BB or CD137) signaling, 28,216-218 or the CD27 agonist varlilumab; 28,216,219,220 and immunomodulatory agents such as lenalidomide.…”
Section: Ongoing Clinical Trialsmentioning
confidence: 99%
“…Such anti-tumor biological effects were shown to be directly correlated with induction of immunological cell death (ICD), enhanced T cell response and reduction of the immune suppressive Tregs cell population. 20,46 To date, more than 50 clinical trials of metronomic chemotherapy have been reported in patients affected by different cancers showing an enhancement of anti-tumor immunity. 23 However, only four clinical trials evaluating metronomic chemotherapy in HCC have been registered to date.…”
Section: Metronomic Chemotherapy In Hccmentioning
confidence: 99%
“…90,91 Chemotherapy can improve anti-tumor effects of cancer vaccines not only by overcoming the immune-suppression, but also by enhancing cross-presentation of tumor antigens as well as increasing the number of effector cells in the tumor microenvironment. 20,46,[92][93][94] Combination of low-dose metronomic chemotherapy and cancer vaccines could represent a potentially attractive option for HCC patients, given the strong immunosuppressive microenvironment in the liver for the presence of several immunosuppressive cells such as CD4 + CD25 + regulatory T cells, 95 which are known to suppress the function of antigenspecific T cell responses and are increased in patients with HCC. 96 Greten TF et al have demonstrated that low-dose cyclophosphamide systemic treatment, but not the full dose, decreases the frequency and suppressor function of circulating CD4 + CD25 + Foxp3 + regulatory T cells in peripheral blood and unmasks α-fetoprotein-specific CD4 + T-cell responses in patients with advanced HCC.…”
Section: Enhancing Cancer Vaccine Efficacy In Hcc By Combinatorial Stmentioning
confidence: 99%